Meta Analisis: Creative Problem Solving: Hasil Riset - Ayu Nur Avina; Astri Sundari; Bunga Casandra; Dedi Candra; Sinta Agustina; Sriyani Sriyani; Yola Bidara; Zulfah Zulfah (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Mathematical problem solving ability is one of the abilities that must be possessed by students in learning mathematics. The right learning model and high self-efficacy are factors that affect mathematical problem-solving abilities. This study aims to determine the effect of the Creative Problem Solving learning model on students' mathematical problem solving abilities. The methods used are several methods with a total sample of 8 journals. The data analyzed were junior and senior high school students, this research is a quantitative research type of experiment that is more effective if used at the junior high school level, if viewed from the material, the CPS learning model is more effective if the Fibbonacci material. Meanwhile, other research shows that CPS has a high influence on Problem Solving Skills.